Role of mineral-forming bacteria in mangrove rhizosphere in enhancing coastal soil stability, carbon sequestration, and heavy metals removal - Afrah Siddique (19724656) (2025)
Mangrove forests are found in intertidal zones of tropical and subtropical regions, playing crucial roles in coastal protection. They serve as natural buffers against wave dynamics, effectively mitigating coastal erosion. Despite covering a small fraction of coastal areas, mangrove forests sequester more carbon dioxide compared to terrestrial vegetation. However, they face significant pressures from both natural forces and human activities, such as coastal development and industrialization, leading to contamination with organic and inorganic pollutants. The accumulation of toxic metals in mangrove ecosystems is of particular concern. This poses significant risks to these forests, which serve as vital habitats and nurseries for marine organisms. Heavy metals accumulate in fish and can potentially enter human food chains through consumption. Mangroves are capable of adapting stressful conditions due to their interaction with soil microorganisms. Mineral-forming bacteria residing in the rhizosphere of mangrove trees play a pivotal role in this context. These bacteria aid in stabilizing heavy metals through mineral precipitation and convert inorganic carbon into a stable carbonate mineral, contributing to carbon sequestration. The biomineralization enhances sediment stability and supports the overall resilience of mangrove ecosystem. While the microbial processes hold a great promise, their role remain underexplored and not fully integrated into the current restoration strategies. Bridging this knowledge gap through interdisciplinary research is essential for developing more sustainable and effective approaches to mangrove conservation. Other Information Published in: Earth-Science Reviews License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.earscirev.2025.105151